Strength training reduces lipid accumulation in liver of obese Wistar rats - dos Santos, Giulia Fonseca [UNESP]; Veras, Allice Santos Cruz [UNESP]; de Freitas, Marcelo Conrado [UNESP]; McCabe, James; Seraphim, Patrícia Monteiro [UNESP]; Teixeira, Giovana Rampazzo [UNESP] (Elsevier, 2019)
Obesity has a positive relation to non-alcoholic fatty liver disease (NAFLD) and studies have demonstrated that strength training can regulate lipid accumulation in the hepatocytes of obese rats. Aims: Our aim is to evaluate the effects of high fat diet and strength training on markers of oxidation and lipogenesis in the liver of Wistar rats. Main methods: Forty Wistar rats were divided into four groups (n = 10): control (CTL), strength training (TR), high fat diet consumption (HF) and high fat diet consumption with strength training (HFT). Animals were subjected to physical strength training and high fat diet consumption for 12 weeks, 3 session per week. Then, the animals were euthanized, and liver markers were evaluated via immunolabeling. Key findings: Our results indicated that strength training reduced the expression of adiposity as well as the accumulation of glycogen and lipids in the liver. This reduction of fatty acid (FA) stored in hepatocytes is related to reduction of proteins linked to β-oxidation such as Fas/CD95, LIMP-II and CD36, as well as other proteins linked to lipogeneses such as SREBP-1. Significance: Finally, we observed that high fat diet can alter lipogenesis and reduce β-oxidation promoted hepatic fat accumulation. In conclusion, there was a reduction of obesity-related hepatic lipogenesis after 12 weeks of strength training.
Keywords: Anaerobic training; CD36; Liver; Obesity; SREBP-1; Strength training